Inter-set stretch: A potential time-efficient strategy for enhancing skeletal muscle adaptations - Schoenfeld, Brad J.; Wackerhage, Henning; De Souza, Eduardo (Frontiers in Sports and Active Living, 2022)
Time is considered a primary barrier to exercise adherence. Therefore, developing time-efficient resistance training (RT) strategies that optimize muscular adaptations is of primary interest to practitioners. A novel approach to the problem involves combining intensive stretch protocols with RT. Conceivably, integrating stretch into the inter-set period may provide an added stimulus for muscle growth without increasing session duration. Mechanistically, stretch can regulate anabolic signaling via both active and passive force sensors. Emerging evidence indicates that both lengthening contractions against a high load as well as passive stretch can acutely activate anabolic intracellular signaling pathways involved in muscle hypertrophy. Although longitudinal research investigating the effects of stretching between RT sets is limited, some evidence suggests it may in fact enhance hypertrophic adaptations. Accordingly, the purpose of this paper is threefold: (1) to review how the active force of a muscle contraction and the force of a passive stretched are sensed; (2) to present evidence for the effectiveness of RT with inter-set stretch for muscle hypertrophy (3) to provide practical recommendations for application of inter-set stretch in program design as well as directions for future research.